Pure Sn coatings produced by pulse plating from stannate bath - Sharma, Ashutosh; Seo, Hyungtak; Ahn, Byungmin (Coatings, 2020)
We have produced pure Sn coatings from an alkaline bath plating. The plating bath was composed of sodium stannate and sodium hydroxide with sorbitol as an additive. The experiments were performed with a potentiostat/galvanostat at various current densities from 5-25 mA/cm2. The morphology of the coatings, thickness, plating rate, and microhardness were evaluated. Furthermore the wetting of the Sn coatings on a Cu substrate was also assessed by area spread ratio measurements after reflow at 250 °C. The resultant coatings were very smooth and shiny. Initially, the plating morphology was uneven and a nodular type, which further improved with increasing current density up to 15 mA/cm2. The plating rate and thickness were the maximum at a current density of 15 mA/cm2. The coatings had higher strength and solderability at 15 mA/cm2 due to the improved microstructure and plating rate.
Keywords: Alkaline; Coatings; Electrolyte; Microstructure; Surface finish; Tin